Ethical and Philosophical Analysis of Conditional Death Sentence Implementation under Article 100 of Law Number 1 of 2023 - Wawan Suprawan; Yuyut Prayuti (Research Horizon, 2026)
Law Number 1 of 2023 introduces a conditional death penalty system that allows the suspension of executions for a ten-year probationary period, with the possibility of conversion into life imprisonment based on rehabilitation. This research analyzes the ethical legitimacy and philosophical foundations of this “middle-way” approach, specifically evaluating its alignment with human rights principles and the ultimate objectives of punishment. Using a normative-juridical method with statutory and conceptual approaches, the study examined Law Number 1 of 2023 and relevant human rights instruments. The findings indicated that while the conditional death penalty is presented as a humanization of criminal law, it creates profound ethical tensions. The ten-year waiting period induces extreme psychological suffering, often termed the “death row phenomenon”, which may constitute inhuman treatment. Philosophically, Article 100 reveals a conflict between retributive justice and rehabilitative goals. Furthermore, the state’s role as an arbiter of life remains contested under international human rights standards. The study concludes that this provision serves as a pragmatic political compromise but requires rigorous safeguards to prevent administrative arbitrariness and ensure substantive justice.